The therapeutic effect of acupuncture in the treatment of chemotherapy-induced peripheral neuropathy: a randomized controlled trial - Xu, Jinqun; Zhang, Qing; Xue, Na; Zhang, Cui; Xu, Weiru (Frontiers in Oncology, 2025)
IntroductionEffective treatments for preventing and treating chemotherapy-induced peripheral neuropathy (CIPN) are still under exploration. Acupuncture in the treatment of CIPN requires more clinical trial data. This study aimed to evaluate the therapeutic effect of acupuncture on CIPN and explore its efficacy and safety in improving peripheral neuropathy.MethodsA randomized controlled trial was conducted from May 2021 to June 2023. Eligible patients were randomly divided into a verum acupuncture group and a sham acupuncture group at a 1:1 ratio with sealed opaque envelopes. The patients of both the two groups took oral mecobalamin tablets, 0.5 mg, three times a day for 2 weeks. Participants received acupuncture treatment three times a week for 2 weeks. The primary outcome was evaluated using the National Cancer Institute Common Terminology Criteria for Adverse Events (NCI-CTCAE) 3.0. The secondary outcomes were assessed using the European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire-CIPN twenty-item subscale (QLQ-CIPN20), Numerical Rating Scale (NRS), Traditional Chinese Medicine (TCM) syndrome score, and nerve conduction study (NCS) testing. Assessments were conducted at baseline, 1 week, and 2 weeks.ResultsAll 70 participants were recruited and randomized. In the end, 68 patients were included in the datasets and received verum acupuncture (n = 34) or sham acupuncture (n = 34). After 2 weeks of treatment and follow-up, a statistically significant difference was found in the NCI-CTCAE scores between the two groups (p = 0.02). Baseline-to-2-week assessment scores improved significantly in the intervention group (vs. controls) on EORTC QLQ-CIPN20 (p = 0.02), NRS scores (p = 0.03), TCM syndrome scores (p = 0.04), and sensory nerve action potential (SNAP) of median and peroneal nerves, sensory nerve conduction velocity (SNCV) and motor nerve conduction velocity (MNCV) of peroneal nerves (p < 0.05). No serious adverse events were reported.ConclusionThis study supports the feasibility of acupuncture combined with medication as an intervention for patients with CIPN and confirms its efficacy and safety in improving peripheral neuropathy.Clinical Trial RegistrationThe Chinese Clinical Trial Registry, identifier ChiCTR2100045762.